Respuesta :

Answer:

y = ± [tex]\sqrt{\frac{a-x}{2b} }[/tex]

Step-by-step explanation:

Given

x = a - 2by² ( subtract a from both sides )

x - a = - 2by² ( multiply through by - 1 to clear the leading negative )

a - x = 2by² ( divide both sides by 2b )

[tex]\frac{a-x}{2b}[/tex] = y² ( take the square root of both sides )

y = ± [tex]\sqrt{\frac{a-x}{2b} }[/tex]

Making y the subject of the formula, [tex]x = a - 2by^2[/tex] , the answer would be:

[tex]\mathbf{y = \sqrt{\frac{x - a}{-2b}} }[/tex]

Given the formula: [tex]x = a - 2by^2[/tex],

Required:

Making y the subject of the formula

This is done as shown below:

[tex]x = a - 2by^2[/tex]

  • Subtract a from both sides

[tex]x - a = - 2by^2[/tex]

  • Divide both sides by -2b

[tex]\frac{x - a}{-2b} = y^2[/tex]

  • Take the square root of both sides

[tex]\sqrt{\frac{x - a}{-2b}} = y\\\\\\\mathbf{y = \sqrt{\frac{x - a}{-2b}} }[/tex]

Therefore, making y the subject of the formula, [tex]x = a - 2by^2[/tex] , the answer would be:  [tex]\mathbf{y = \sqrt{\frac{x - a}{-2b}} }[/tex]

Learn more here:

https://brainly.com/question/19557491